Long-term impacts of integrated nutrient management with equivalent nutrient doses to mineral fertilization on soil organic carbon sequestration in a sub-tropical Alfisol of India. Issue 5 (1st October 2020) - Trivedi, Ankita; Bhattacharyya, Ranjan; Biswas, D. R.; Das, S.; Das, T. K.; Mahapatra, P.; Shahi, D. K.; Sharma, C.
Abstract: Limited evidence is available on carbon sequestration potential of long-term integrated nutrient management (INM) versus mineral fertilization, when equivalent amounts of nutrients were added. Hence, this study was carried out to understand the impact of 60 years of INM with adjusted nutrient doses and mineral fertilization in an Alfisol in a maize ( Zea mays L.)-wheat ( Triticum aestivum L.) system on soil organic carbon (SOC) sequestration in surface (0–30 cm) and deep (30–60 cm) soil layers. Conventional tillage was done twice before sowing of both maize and wheat using a spade. In farmyard manure (FYM) and lime treated plots (FYMP'K'L: plots with nitrogen (N) applied in terms of FYM; additional dose of phosphorus (P) and potassium (K) and lime) total SOC concentration was nearly 83% higher than unfertilized control plots. The FYMP'K'L plots had ∼11% more total SOC concentration than plots treated with mineral fertilizer and lime (NPKL: recommended dose of N, P, K and lime) in the 0–30 cm soil layer. Labile C, including KMnO4 -C, was more in plots with FYM than NPKL plots, whereas the recalcitrant C stock was more in NPKL than FYM treated plots. In the 0–60 cm soil layer, the labile C stock was highest in FYMP'K'L plots, but the recalcitrant C stock was highest in NPKL. Total SOC accumulation rate (over unfertilized control plots) was highest for FYMP'K'L plots (0.38 Mg ha −1  year −1 ) in the surface soil layer, whereas SOC sequestration rate was highest in NPKL plots (0.18 Mg ha −1  year −1 ) in the deep layer and in the 0–60 cm layer. Overall, although NPKL management practice had the highest C sequestration in the 0–60 cm layer, FYMP'K'L had the best CMI and labile C pools. Thus, resource poor farmers need not to use full doses of NPK and FYM for soil C management in the region.